2014
DOI: 10.1111/cbdd.12345
|View full text |Cite
|
Sign up to set email alerts
|

Aporphinoid Antagonists of 5‐HT2A Receptors: Further Evaluation of Ring A Substituents and the Size of Ring C

Abstract: A series of ring A modified analogs of nantenine as well as structural variants in ring C were synthesized and evaluated for antagonist activity at 5-HT2A and α1A receptors. Halogenation improves 5-HT2A antagonist potency in molecules containing a C1 methoxyl/C2 methoxyl or C1 methoxyl/C2 hydroxyl moiety. Bromination or iodination (but not chlorination) with the latter moiety also significantly increased α1A antagonist potency. Homologation or contraction of ring C adversely affected antagonist activity at bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…By a combinatorial study using both the docking and MD analyses, as well as a detailed comparison between these results, it is demonstrated that the present docking model is reliable in reflecting the particular binding mechanism in the 5-HT 2A receptor active site. To further explore the interaction features of general 5-HT 2A antagonists and the binding model of arylpiperazine derivatives with the target protein, a comparison of previously-reported docking studies of known 5-HT 2A antagonists with the ones assessed in our current work was conducted [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Above Table 2 summarizes the important information obtained from these studies, for purpose to compare their similarities and differences, with their representative structures of the ligands summarized in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By a combinatorial study using both the docking and MD analyses, as well as a detailed comparison between these results, it is demonstrated that the present docking model is reliable in reflecting the particular binding mechanism in the 5-HT 2A receptor active site. To further explore the interaction features of general 5-HT 2A antagonists and the binding model of arylpiperazine derivatives with the target protein, a comparison of previously-reported docking studies of known 5-HT 2A antagonists with the ones assessed in our current work was conducted [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Above Table 2 summarizes the important information obtained from these studies, for purpose to compare their similarities and differences, with their representative structures of the ligands summarized in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to that an accurate 3D structure of the receptor is essential for docking analysis, and until now an X-ray structure of 5-HT 2A receptor is, yet, still unavailable, the homology modeling becomes a necessity in the present work. In addition, since, to our best knowledge, almost all (which is actually, 7 out of 9 as shown in Table 2 ) current crystal structures of 5-HT 2A receptor built by homology modeling for further docking analysis were based on the structure of β 2 -adrenergic receptor as a template [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], for purpose of a well comparison with previously-reported docking studies of known 5-HT 2A antagonists, the structure of 5-HT 2A receptor we used presently still adopted the structure of β 2 -adrenergic receptor as the homology modeling’s template. Actually, this structure was built by Ísberg et al, where the 5-HT 2A receptor model was constructed using the β 2 -adrenergic receptor (PDB entry 2RH1) as the main template, and then further modified to incorporate template features from the active G-protein-bound opsin crystal structure (PDB entry 3DQB) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…1517 The 5-HT 2A receptor plays a significant role in various neuropsychiatric disorders such as schizophrenia, anxiety depression and psychostimulant abuse. 1822 Selective 5-HT 2A antagonists are being pursued as novel therapeutics to treat sleep disorders.…”
mentioning
confidence: 99%
“…In that context, our previous SAR studies based on the aporphine alkaloid nantenine ( 4 , Figure 2) have resulted in the identification of new aporphinoid 5-HT 2A receptor antagonists with significantly improved affinity and selectivity as compared to nantenine. 10-13 In continuing efforts in that vein, we wish to report an SAR study that has resulted in the identification of the most potent aporphine-derived 5-HT 2A receptor antagonist known to date.…”
mentioning
confidence: 99%
“…11,13,14 These studies have shown that substituents at the C1 position of nantenine may be manipulated to improve 5-HT 2A affinity and selectivity. n -Alkyl substituents were particularly well tolerated.…”
mentioning
confidence: 99%